TRANSFORMASI DIGITAL DI PEDESAAN: PERAN BUMDES DALAM PENGUATAN AKSES INTERNET WARGA DESA KROCOK KABUPATEN BLORA - Aras Aras; Kuncoro Bayu Prasetyo (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2025)
This study aims to explore digital transformation in rural areas through the provision of village WiFi network services in Krocok Village, Japah District, Blora Regency, which is managed by the Kerjaya Krasa Village-Owned Enterprise. The main problem studied is how digital transformation takes place and its impact on the socio-economic life of the community. This study uses a qualitative method with a naturalistic approach. Data were collected through semi-structured interviews, direct observation, and documentation of the activities of providing and utilizing village internet services. The results of the study show that village WiFi services contribute to increasing access to information, citizen productivity, and Village Original Income. The conclusion of this study states that digital transformation through village WiFi management is a strategic means of strengthening digital development and improving the welfare of rural communities. This study also found a number of challenges, such as limited network infrastructure in certain areas and the existence of community groups that do not fully understand digital technology.